PENGEMBANGAN BAHAN AJAR SENAM RITMIK PADA SISWA SD KARTIKA XIV – I KOTA BANDA ACEH - Fadly, Hendri; Azwar, Edi; Imam Bahesty, Dicky; Amelia Sofya, Bungsu (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2025)
Gymnastics is one of the materials in physical education that can be influenced by factors, namely the use of materials. Teaching materials greatly affect learning outcomes so it is necessary to develop teaching materials in order to achieve the goals of social justice well. This research aims to develop rhythmic gymnastics teaching materials for students of SD Kartika XIV-1 Banda Aceh City. This type of research is classified as a type of development research with observation techniques, interviews, expert validation and trials, while research design with observation, potential theoretical design problems, product design, expert validation, design revision, trial, product revision and the resulting product. The subjects in this study are 30 students of SD Kartika class V. The process of developing teaching materials is carried out by validation by experts and revision of teaching materials after validation. The data that has been collected is then analyzed using quantitative. Based on the results of the research that has been obtained based on analysis and discussion, it can be concluded that the development of rhythmic gymnastics in SD Kartika grade V is a teaching material that can be used in learning rhythmic gymnastics because it has a validity level with a table of 0.243 so that it can be used for the development of rhythmic gymnastics and has a very high valid level with an alpha point of 0.992 so that it can be used in the development of rhythmic gymnastics in students of Kartika Elementary School in the process of daily activities.